2009
DOI: 10.1007/s12257-008-0244-8
|View full text |Cite
|
Sign up to set email alerts
|

Excellent laundry detergent compatibility and high dehairing ability of the Bacillus pumilus CBS alkaline proteinase (SAPB)

Abstract: ^Äëíê~Åí= The newly Tunisian soil-isolated bacterium, producing the alkaline proteinase termed SAPB that was already purified and characterized [1], was assigned as _~Åáääìë=éìãáäìë=CBS strain on the basis of biochemical properties and 16S rRNA gene sequencing. The maximum protease activity recorded after 24 h of incubation in an optimized medium at 37°C was 6,500 U/mL in shaking flask culture and 25,000 U/mL in fermentor. SAPB showed excellent stability and compatibility in laundry detergent retaining more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…The non-treated enzyme was rapidly inactivated, losing about 50% of its initial activity after 2 months of incubation. Moreover, compared to the treated enzyme and in the absence of additives, 1% xylitol clearly enhanced SAPB stability during storage within the Det solid detergent (Jaouadi et al, 2009). In fact, after being incubated for 12 months at room temperature in the presence and absence of xylitol, the spray-dried enzyme retained 68 and 55% of its initial activity, respectively.…”
Section: Storage Stability Of the Spray-dried And Lyophilized Sapbmentioning
confidence: 96%
See 4 more Smart Citations
“…The non-treated enzyme was rapidly inactivated, losing about 50% of its initial activity after 2 months of incubation. Moreover, compared to the treated enzyme and in the absence of additives, 1% xylitol clearly enhanced SAPB stability during storage within the Det solid detergent (Jaouadi et al, 2009). In fact, after being incubated for 12 months at room temperature in the presence and absence of xylitol, the spray-dried enzyme retained 68 and 55% of its initial activity, respectively.…”
Section: Storage Stability Of the Spray-dried And Lyophilized Sapbmentioning
confidence: 96%
“…The findings from these assays revealed that the blood and chocolate stain removal levels achieved with the use of SAPB alone were more effective than the ones obtained with detergent (Det) alone. In fact, SAPB facilitated the release of proteinacious materials in a much easier way than the commercialized SB 309 protease (Jaouadi et al, 2009). Furthermore, the combination of SAPB and the Det detergent resulted in complete stain removal (Fig.…”
Section: Wash Performance Analysis Of Sapbmentioning
confidence: 96%
See 3 more Smart Citations